Colmena: collection of edaphic microorganisms and native endophytes, to contribute to national food security - de los Santos Villalobos, Sergio; Parra Cota, Fannie Isela; Herrera Sepúlveda, Angélica; Valenzuela Aragón, Brenda; Estrada Mora, Juan Carlos (Revista Mexicana de Ciencias Agrícolas, 2018)
COLMENA (www.itson.mx/colmena), is a collection of microorganisms focused on the conservation, classification, characterization, and transfer of native microorganisms isolated from diverse agro-systems, and other habitats. The objective of this collection is to protect the microbial diversity associated with changes in land use, reducing the degradation of soils. So far, soil microorganisms from two important agricultural regions in Mexico have been isolated, the Yaqui Valley, Sonora and the Valley of Fuerte, Sinaloa. Currently, COLMENA conserves approximately 1 446 strains of soil microorganisms associated with various agricultural crops, such as: wheat (448), corn (313), alfalfa (54), broccoli (51), beans (35), among others. Recently, the taxonomic classification of 353 bacterial and fungal strains-through the amplification of the 16S RNAr and 5.8S RNAr genes- has been concluded, noting that the most abundant bacterial genera are Bacillus (27%), Pseudomonas (8%) and Stenotrophomonas. (6%), while the most abundant fungal genera were Aspergillus (8%), Penicillium (3%) and Myrothecium (3%). On the other hand, the metabolic characterization of a fraction of the collection was also carried out, finding that 3% of the microbial collection has the capacity to produce indoles (> 5 mg/L), the solubilization of phosphorus and the production of siderophores it was observed in 36% and 61% of the strains analyzed (396), respectively. Only 3% of the total microbial collection has been identified as producing cellulases and 11% of a total of 258 strains analyzed showed β-hemolysis. These results show the versatility of these microbial strains as potential cost-effective alternatives for agro-industrial practices, focused on contributing to global food security.